Factorization of Periodic Locally Solvable Groups by Locally Nilpotent and Nilpotent Subgroups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish a series of new results concerning periodic locally solvable and finite solvable groups G = AB with locally nilpotent or nilpotent subgroups A and B.